Peningkatan Kualitas Hidup Lansia Melalui Penerapan Pola Hidup Sehat di Desa Moncongloe Bulu - Julia Fitrianingsih (Pusat Riset dan Inovasi Nasional, 2022)
Elderly is synonymous with various declines in health status, especially physical health status. Various theories about the aging process show the same thing. The health status of the elderly which declines with age will affect the quality of life of the elderly. Increasing age will be accompanied by the emergence of various diseases, decreased body function, body balance and the risk of falling. The decline in the health status of the elderly is contrary to the desire of the elderly to remain healthy, independent and able to carry out activities as usual, such as bathing, dressing, moving independently. This activity aims to provide information to the public about the importance of maintaining reproductive health in improving the quality of life. This educational process uses the lecture method with the help of powerpoints and leaflets. The results obtained from this activity are that the youth participating in this service activity become more aware and know more about how to improve the quality of life, especially during this pandemic. The assessment is based on the response and enthusiasm of the participants in receiving the material provided. Including positive responses from participants in answering questions correctly when asked questions by the presenters.